If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 185x * 45y + 60y = 10500x Reorder the terms for easier multiplication: 185 * 45x * y + 60y = 10500x Multiply 185 * 45 8325x * y + 60y = 10500x Multiply x * y 8325xy + 60y = 10500x Solving 8325xy + 60y = 10500x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10500x' to each side of the equation. 8325xy + -10500x + 60y = 10500x + -10500x Reorder the terms: -10500x + 8325xy + 60y = 10500x + -10500x Combine like terms: 10500x + -10500x = 0 -10500x + 8325xy + 60y = 0 Add '-60y' to each side of the equation. -10500x + 8325xy + 60y + -60y = 0 + -60y Combine like terms: 60y + -60y = 0 -10500x + 8325xy + 0 = 0 + -60y -10500x + 8325xy = 0 + -60y Remove the zero: -10500x + 8325xy = -60y Combine like terms: -60y + 60y = 0 -10500x + 8325xy + 60y = 0 Factor out the Greatest Common Factor (GCF), '15'. 15(-700x + 555xy + 4y) = 0 Ignore the factor 15.Subproblem 1
Set the factor '(-700x + 555xy + 4y)' equal to zero and attempt to solve: Simplifying -700x + 555xy + 4y = 0 Solving -700x + 555xy + 4y = 0 Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -700x + 555xy + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 -700x + 555xy + 0 = 0 + -4y -700x + 555xy = 0 + -4y Remove the zero: -700x + 555xy = -4y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x-12+x=124 | | -2(-6a-4)-2=-90 | | 8z-72=8 | | 6x^5+17x^4-x^2+3x+3=0 | | 6+4x=-4x+22 | | 4(x-2)=-3(5-x) | | 5x+2x-8=41 | | Z^2=8-8i | | 5x-6+3=7 | | 5x+2x-8=42 | | 15x=17+8x-24 | | -19=13x+2 | | 6c+3+11=8c | | 45x+60x+185y=10500 | | 0.5y+9=31 | | 3.96=-44z | | X+(-5)=18 | | 0.5y+9= | | -2.5x-1.7=-16.4 | | 3x+2(x+7)=86 | | 3x-5-x+2=13 | | 8.5=4x+5 | | X+(-4)=-25 | | 2x-5=64 | | -4t+24=16 | | 49x+1=48x+3 | | 2.86-21.1= | | (-18)=5x-8 | | 2r-r=9 | | =-3/7x-1/7 | | 5(0)=15+3y | | x+6=-5(x+6) |